PEMBANGUNAN APLIKASI E-COMMERCE PADA COUNTER HANDPHONE BANDAR LAMPUNG - Ulfa Fitriyani Yapan; Ivan Rinaldo (Universitas Mitra Indonesia, 2021)
AbstractThe cellphone sales website is basically presenting an application that is designed into a computerized modeling format that is used to provide online cell phone sales information to the public and to expand the marketing are a which is expected to be able to increase the number of cell phone sales being marketed. From the research analysis carried out, the design of the mobile phone sales application at the web-based Kunci Urip Cell counter uses the SDLC system development method, which is a system whose information system development process starts from the initial concept to the implementation stage and the data collection technique uses observation and interview techniques. Based on the description described, it can be concluded that withth is web site application sales will be more efficient because it will make it easier for customers to make purchases anywhere and anytime without having to come to the counter. And in order to support the smooth running of the work process, there searchers suggest the need to take care of the software (software) and hardware (hardware) in order to keep it safe from damage or computer viruses. Keywords : SDLC, Handphone, Online